2005
DOI: 10.1177/1420326x05050675
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos-containing Floor Tile and Mastic Abatement: Is there Enough Exposure to Cause Asbestos-related Disease?

Abstract: Chrysotile asbestos has been reported as a constituent of both floor tiles and mastic. In consequence, asbestos-containing floor tiles and mastic have been identified by regulatory agencies as hazardous materials. The reason for this categorisation is the suggested potential for these materials to cause asbestos-related diseases and as a result special handling has been prescribed. However, studies have reported that little airborne asbestos exposure occurs during abatement of these materials. Evaluation of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…The average airborne asbestos concentrations reported in this meta-analysis for both a worker performing floor tile tasks, as well as a bystander working in the vicinity of such activity, were below both the current and all previous US occupational asbestos standards. These results are consistent with those reported by Lange [57] over a decade ago, but those did not break down exposures by activity and task.…”
Section: Discussionsupporting
confidence: 93%
“…The average airborne asbestos concentrations reported in this meta-analysis for both a worker performing floor tile tasks, as well as a bystander working in the vicinity of such activity, were below both the current and all previous US occupational asbestos standards. These results are consistent with those reported by Lange [57] over a decade ago, but those did not break down exposures by activity and task.…”
Section: Discussionsupporting
confidence: 93%
“…According to a study conducted by Lange [ 19 ], it was found that during the demolition of floors and mastics containing chrysotile, there is a low exposure to airborne asbestos.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical studies indicate a direct correlation between the asbestos consumption and the number of asbestos-related diseases in a country, and they project substantial increases in asbestos-related diseases in many countries [16][17][18][19][20]. Environmental and occupational health studies indicate that airborne fibre concentrations must be at certain levels in work environments [21][22][23][24][25][26][27][28][29]. As a result of scientific evidence, mining, processing and use of asbestos minerals are regulated in many nations around the world.…”
Section: Introductionmentioning
confidence: 99%